A Research Agenda for Improving Science and Mathematics Education in Rural Schools - Hobart L. Harmon; Stephen A. Henderson; Wimberly C. Royster (Journal of Research in Rural Education, 2003)
We present the outcome of a conference supported by the National Science Foundation (NFS) and conducted by the Appalachion Rural Systematic Initiative. The purpose of this conference was to establish a research agenda for studying factors that impact the student learning process and student achievement in mathematics and science in rural schools. The 47 conference participants included rural, science, mathematics and technology educators from across the country representing universities, public schools, and NSF-sponsored Rural Systemic Initiatives. Researchable questions that emerged from conference discussions are grouped into seven categories: community support, instructional resources, leadership and school reform, professional development, preservice and induction, curriculum and instruction, and database.